Analisis Yuridis Terhadap Penulisan Akta Notaris Dalam Sela-Sela Kosong Buku Pendaftaran Akta - Yunanto Yunanto; Novira Maharani Sukma; Alya Regita Ratna Putri (Notarius, 2021)
The authority of a notary that is given to create an opportunity for a violation of the authentic deed includes recording the notary deed between deeds that have been recorded in the form of notary deed. So that the implementation of the duties of the notary office needs to be monitored. Deeds that are recorded in the spacing guidelines between notary deeds that have been recorded in the list of deeds will have the strength of evidence as deeds that do not meet formal requirements and are canceled because they contain elements of fraud. As a result, notaries must be responsible for civil sanctions, administrative sanctions and criminal sanctions. Journals are compiled using normative juridical research methods with a statutory approach. Based on the survey results, it is known that there are very dangerous consequences if the notary deed and the deed recorded within the distance between the deeds have been recorded in the notary deed register. In addition to the legal status of a deed which is reduced to a fraudulent deed and is null and void which cannot be used as perfect evidence, the deed also contradicts the obligations of notaries as stipulated in Article 15 of Law Number 2 of 2014, namely the mandatory date for notaries. ensure certainty and timing.Keywords: blank between the register of deed; deed under hand; notarial deedAbstrakPemberian kewenangan notaris guna menciptakan peluang terjadinya pelanggaran akta otentik diantarana mencatat akta notaris disela-sela akta yang telah dibukukan register akta notaris kosong. Jadi pelaksanaan tugas kantor notaris perlu dimonitor. Akta yang tercatat pada pedoman spasi antar akta notaris yang sudah dilakukan pencatatan pada daftar akta tersebut akan mempunyai kekuatan alat bukti sebagai akta yang berada di bawah akibat tidak terpenuhinya persyaratan formil dan batal karena mengandung unsur kecurangan. Akibatnya, notaris harus bertanggung jawab atas sanksi perdata, sanksi administratif, dan sanksi pidana. Jurnal disusun dengan metode penelitian yuridis normatif dengan pendekatan perundang-undangan. Berdasarkan hasil survey diketahui bahwa terdapat akibat yang sangat berbahaya jika akta notaris dan akta yang tercatat dalam pedoman spasi antar akta sudah dilakukan pencatatan pada daftar akta notaris. Sementara status hukum akta diturunkan kepada akta dibawah tangan serta batal demi hukum yang tidak bisa menjadi kesempurnaan alat pembuktian, akta itu berlawanan pada kewajiban notaris yang ditetapkan pada Pasal 15 Undang-Undang Nomor 2 Tahun 2014 yang merupakan tanggal wajib notaris. memastikan ketetapan dan waktu.Kata kunci: sela-sela kosong buku daftar akta notaris; akta di bawah tangan; akta notaris